1998
DOI: 10.1063/1.122161
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions of Pd/Si0.76Ge0.24 by pulsed KrF laser annealing

Abstract: The interfacial reactions of Pd/Si0.76Ge0.24 were studied by pulsed KrF laser annealing as a function of energy density and pulse number. At an energy density of 0.1–0.4 J/cm2, a continuous germanosilicide layer composed of a low-temperature phase, Pd2(Si1−xGex), and a high-temperature phase, Pd(Si1−xGex), was formed. In contrast to vacuum annealing, Ge segregation out of the germanosilicide layer and the strain relaxation of the residual Si0.76Ge0.24 film could be effectively suppressed by pulsed KrF laser an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Similar results were observed in the Pd/Si 0.76 Ge 0.24 system. 28 Those results imply that during the interfacial reactions of metal-Si 1−x Ge x the strain relaxation of the residual Si 1−x Ge x film can be suppressed by inhibiting Ge segregation out of the germanosilicide via pulsed KrF laser annealing. In the present study, we concluded that multiple pulse annealing at 0.2 J/cm 2 is an effective method to produce a smooth Co(Si 0.76 Ge 0.24 ) 2 film without Ge segregation out of the germanosilicide and inducing strain relaxation in the residual Si 0.76 Ge 0.24 film.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…Similar results were observed in the Pd/Si 0.76 Ge 0.24 system. 28 Those results imply that during the interfacial reactions of metal-Si 1−x Ge x the strain relaxation of the residual Si 1−x Ge x film can be suppressed by inhibiting Ge segregation out of the germanosilicide via pulsed KrF laser annealing. In the present study, we concluded that multiple pulse annealing at 0.2 J/cm 2 is an effective method to produce a smooth Co(Si 0.76 Ge 0.24 ) 2 film without Ge segregation out of the germanosilicide and inducing strain relaxation in the residual Si 0.76 Ge 0.24 film.…”
Section: Resultsmentioning
confidence: 71%
“…Strain relaxation might be induced by the chemical inhomogeneities, e.g., Ge segregation, and defects present in the interface between the germanosilicide and the unreacted Si 1−x Ge x film. 7,17,[26][27][28] At 0.6 J/cm 2 three germanosilicide layers were still present, and some Ge further diffused to the Si substrate, indicating that the melting depth exceeded the total thickness of the asdeposited Co layer (∼25 nm) and the as-grown Si 0.76 Ge 0.24 film (∼150 nm). Meanwhile the inhomogeneous distribution of Co in the reacted region was significantly improved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excimer lasers have been used to convert amorphous Si to Poly-Si for the fabrication of thin film transistors for flat panel displays [24], [25]. Additionally, excimer lasers have been used to anneal SiN x films [26], Pd/SiGe contacts [27], and n-GaAs contacts [28].…”
Section: Laser Annealing Of Ybco Thin Filmsmentioning
confidence: 99%